Legal Protection For Consumers In Consumers Electronic Transactions - Yenni Kristin. P (Journal of Law Science, 2020)
The presence of electronic commerce or electronic commerce, not only has a positive impact on the world of trade, especially in Indonesia, but has also given birth to laws against consumers for electronic commerce users. Consumer protection is a term used to describe the legal protection provided to consumers in an effort to meet their needs from things that can harm consumers themselves. By understanding the understanding of the consumer itself, it will be able to know what things are the rights and obligations of the consumer and also the relationship between the consumer and the business actor. Consumer protection in Indonesia is regulated in the Law of the Republic of Indonesia Number 8 of 1999 concerning Consumer Protection. The writing method used is a normative legal research method, namely through library research or library research, namely research conducted by examining library materials related to the problems to be studied. Library materials that are used as sources of research are also called secondary data. The payment system used in electronic commerce must be paid through an electronic system as well, either by using a credit card or debit card. Security by using this system is protected by Law Number 11 of 2008 concerning Information and Electronic Transactions.